Pengelolaan Pembelajaran Kewirausahaan Di SMK Sukawati Gemolong - ICHSANUDIN, Ichsanudin; , Dr. Tjipto Subadi, M.Si; , Drs. Budi Sutrisno, M.Pd (2015)
The purpose of this study were to describe (1) the characteristics of entrepreneurial learning interaction management in vocation Sukawati Gemolong. (2) the characteristics of entrepreneurial activity managemen in the learning of teachers in vocation Sukawati Gemolong. (3) the characteristics of the management of student learning activities in entrepreneurship learning in vocation Sukawati Gemolong. This research is qualitative research and the design of fenomenologic research. The location of this research is in SMK Sukawati Gemolong. Data was collected by observation, interview, and documentation. Model analysis of the data in this study using cross-site analysis methods for description. The results of the study are (1) the interaction of entrepreneurial learning in vocational Sukawati Gemolong largely determined by the teacher and the learner. Interaction of learning occurs in the learning process takes place in the school that occurs between teachers and students and among students with other students, and students with teachers. Interaction that exists between teachers and students accomplished in accordance with the existing timetable. Interaction is the direction from top to bottom. (2) Activities of teachers in delivering the core learning is done by the teacher explained to the students, showing some source materials, using props, provide questions to students, and answer any questions students then use learning methods that have been assigned to the RPP. (3) Student learning activities in entrepreneurial learning a lot done in the classroom with the teacher to listen to the explanation of the theories of entrepreneurship later in the students' learning persipan do with preparing various stationery, and books before learning module starts after starting the learning of students began to record parts important that described by the teacher.